Answer:
Given the system of equations:
.....[1]
.....[2]
We can write equation [1] as;
2(y-x) = 12
Divide both sides by 2 we get;
or
y = x+6 ....[3]
Substitute equation [3] in [2] we get;
Subtract 36 from both sides we have;
Combine like terms;
![2x^2+12x =0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fu0dri7vll4xbsyi900com8yj0qfmvjvry.png)
or
![2x(x+6)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/80qsnta07mm7y4j7svmg9tsormj36wn9uo.png)
By zero product property:
x =0 and x+6 = 0
or
x = 0 and x = -6
now, substitute the given values of x in [3] we have;
for x = 0
y = 0+6 = 6
for x = -6
y = -6 + 6 = 0
Therefore, the solution for the given system of equation is, either (0, 6) or (-6, 0)